2011
DOI: 10.1371/journal.pone.0021916
|View full text |Cite
|
Sign up to set email alerts
|

A New Baurusuchid (Crocodyliformes, Mesoeucrocodylia) from the Late Cretaceous of Brazil and the Phylogeny of Baurusuchidae

Abstract: BackgroundBaurusuchidae is a group of extinct Crocodyliformes with peculiar, dog-faced skulls, hypertrophied canines, and terrestrial, cursorial limb morphologies. Their importance for crocodyliform evolution and biogeography is widely recognized, and many new taxa have been recently described. In most phylogenetic analyses of Mesoeucrocodylia, the entire clade is represented only by Baurusuchus pachecoi, and no work has attempted to study the internal relationships of the group or diagnose the clade and its m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
0
28

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(183 citation statements)
references
References 81 publications
5
150
0
28
Order By: Relevance
“…America (and other regions of Gondwana) has remarkably increased since the original studies of Gasparini in the 1970's and 1980's (Carvalho and Bertini, 1999;Ortega et al, 2000;Campos et al, 2001;Carvalho et al, 2004Carvalho et al, , 2005Carvalho et al, , 2011Pol and Apesteguía, 2005;Nobre and Carvalho, 2006;Andrade and Bertini, 2008;Carvalho, 2009, 2011;Kellner et al, 2009Kellner et al, , 2011aMarinho and Carvalho, 2009;Nascimento and Zaher, 2010;Montefeltro et al, 2011;Martinelli et al, 2012;Marinho et al, 2013). The new discoveries, coupled with the inclusion of both Baurusuchidae and Peirosauridae within Notosuchia in recent phylogenetic studies (e.g., Turner and Sertich, 2010;Pol et al, 2012Pol et al, , 2014, revealed a previously unsuspected diversity of Notosuchian crocodyliforms.…”
Section: The Diversity Of Cretaceous Crocodyliforms From Southmentioning
confidence: 99%
See 3 more Smart Citations
“…America (and other regions of Gondwana) has remarkably increased since the original studies of Gasparini in the 1970's and 1980's (Carvalho and Bertini, 1999;Ortega et al, 2000;Campos et al, 2001;Carvalho et al, 2004Carvalho et al, , 2005Carvalho et al, , 2011Pol and Apesteguía, 2005;Nobre and Carvalho, 2006;Andrade and Bertini, 2008;Carvalho, 2009, 2011;Kellner et al, 2009Kellner et al, , 2011aMarinho and Carvalho, 2009;Nascimento and Zaher, 2010;Montefeltro et al, 2011;Martinelli et al, 2012;Marinho et al, 2013). The new discoveries, coupled with the inclusion of both Baurusuchidae and Peirosauridae within Notosuchia in recent phylogenetic studies (e.g., Turner and Sertich, 2010;Pol et al, 2012Pol et al, , 2014, revealed a previously unsuspected diversity of Notosuchian crocodyliforms.…”
Section: The Diversity Of Cretaceous Crocodyliforms From Southmentioning
confidence: 99%
“…A strong component of recent research on notosuchians has been the use of cladistics analysis for testing the relationships of Notosuchia Pol, 2003;Carvalho et al, 2004;Turner and Sertich, 2010;Andrade et al, 2011;Montefeltro et al, 2011;Pol et al, 2012Pol et al, , 2014. Many of these studies are now corroborating the monophyly of the four Cretaceous clades early recognized by Gasparini for South American forms in pioneer contributions during her early career (i.e., Uruguaysuchidae, Peirosauridae, Baurusuchidae, and a clade allying Notosuchus and closely related forms; Gasparini, 1971Gasparini, , 1972Gasparini, , 1982.…”
Section: The Diversity Of Cretaceous Crocodyliforms From Southmentioning
confidence: 99%
See 2 more Smart Citations
“…Formas hipercarnívoras, como Baurusuchidae e Sebecidae, apresentam como característica marcante a presença de uma dentição claramente zifodonte (sensu Prasad & Broin, 2002), com uma coroa dentária comprimida lateralmente e carenas com serrilha formada por baterias longitudinais de dentículos, num padrão semelhante à dentição encontrada em Theropoda (Pinheiro et al, 2008;Montefeltro et al, 2011;. Algumas filogenias unem estes táxons hipercarnívoros, como Baurusuchus e Sebecus, dentro de um clado mais abrangente, como Sebecosuchia (Pol, 2003) ou Baurusuchoidea (Carvalho et al, 2004), enquanto outras não apontam para uma relação próxima entre os dois grupos, deixando os Sebecidae fora de Notosuchia (Sereno & Larsson, 2009;Holliday & Gardner, 2012).…”
Section: Paleobiologia Dos Notosuchiaunclassified